2010
DOI: 10.1177/1468794110366802
|View full text |Cite
|
Sign up to set email alerts
|

Pluralism in qualitative research: the impact of different researchers and qualitative approaches on the analysis of qualitative data

Abstract: Qualitative approaches to research in psychology and the social sciences are increasingly used. The variety of approaches incorporates different epistemologies, theoretical traditions and practices with associated analysis techniques spanning a range of theoretical and empirical frameworks. Despite the increase in mixed method approaches it is unusual for qualitative methods to be used in combination with each other. The Pluralism in Qualitative Research project (PQR) was developed in order to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 36 publications
(31 reference statements)
3
97
0
3
Order By: Relevance
“…[53] If a group of codes are repeated in a patterned way and in multiple situations, they have potential to become a theme. [20,54] Comparison has the capacity to reveal the link between codes and nominate themes using researchers' intellectual judgment. Testing propositions and asking questions of similarities and differences between codes enable the detection of theme.…”
Section: Comparingmentioning
confidence: 99%
“…[53] If a group of codes are repeated in a patterned way and in multiple situations, they have potential to become a theme. [20,54] Comparison has the capacity to reveal the link between codes and nominate themes using researchers' intellectual judgment. Testing propositions and asking questions of similarities and differences between codes enable the detection of theme.…”
Section: Comparingmentioning
confidence: 99%
“…Frost (2009) showed the different interpretive layers that can be obtained using four different models of narrative analysis. Frost et al (2010) demonstrated the transparency and richness one can obtain when four researchers with different qualitative approaches analyze the same interview and narrate their experiences during the investigation process.…”
Section: Considerando O Narrar E a Psicanálise Como Processos De Elabmentioning
confidence: 99%
“…Some of them focus on the narrative as a process to elaborate life experiences (Bruner, 1990(Bruner, , 2004, while others emphasize its use as a research instrument (Caine, 2010;Frost, 2009;Frost et al, 2010;Melleiro & Gualda, 2004;Paulson, 2010;Riessman, 2008;Vallido, Wilkes, Carter, & Jackson, 2010).…”
Section: Considerando O Narrar E a Psicanálise Como Processos De Elabmentioning
confidence: 99%
See 1 more Smart Citation
“…Further pluralistic qualitative analysis will be used as a form of triangulation to give a holistic understanding of a little researched area (Frost et al, 2010).…”
Section: Designmentioning
confidence: 99%